Literature Review: The Role of Yoga Exercises and William Flexion Exercise on Muscle Activation and Lumbar Stability in Chronic Low Back Pain - Br Ginting, Erma Juana; Rosella Komalasari, Dwi; Wijianto, Wijianto (Rifa'Institute, 2025)
Chronic Low Back Pain (CLBP) is a musculoskeletal disorder that often causes disability and a decrease in quality of life. Non-pharmacological management such as Yoga and William Flexion Exercise (WFE) are effective alternatives to improve lumbar stability and core muscle activation. This study uses a literature review method based on the PRISMA approach on 15 published articles between 2012–2024 that discuss the influence of Yoga and WFE on core muscle activation and lumbar stability in CLBP patients. The results of the study showed that Yoga plays a role in increasing the activation of transversus abdominis and multifidus muscles through an integrative mechanism between postural control, breathing, and body awareness. Meanwhile, WFE effectively strengthens the rectus abdominis and iliopsoas muscles, reduces intradiscal pressure, and decreases pain intensity. The combination of the two exercises has been shown to provide synergistic results in strengthening the stabilizing muscles and significantly reducing pain complaints. Therefore, the integrative approach of Yoga–WFE can be recommended as an effective, safe, and low-cost nonpharmacological rehabilitation strategy for people with CLBP